What happens in the dark? Assessing the temporal control of photo‐mediated controlled radical polymerizations. Issue 3 (8th November 2018) - Dolinski, Neil D.; Page, Zachariah A.; Discekici, Emre H.; Meis, David; Lee, In‐Hwan; Jones, Glen R.; Whitfield, Richard; Pan, Xiangcheng; McCarthy, Blaine G.; Shanmugam, Sivaprakash; Kottisch, Veronika; Fors, Brett P.; et al.
Abstract : A signature of photo‐mediated controlled polymerizations is the ability to modulate the rate of polymerization by turning the light source 'on' and 'off.' However, in many reported systems, growth can be reproducibly observed during dark periods. In this study, emerging photo‐mediated controlled radical polymerizations are evaluated with in situ 1 H NMR monitoring to assess their behavior in the dark. Interestingly, it is observed that Cu‐mediated systems undergo long‐lived, linear growth during dark periods in organic media.